The Use of Borrower-based Measures within Macroprudential Policy: Evidence from the European Economic Area - Lukáš Fiala; Petr Teplý (European Financial and Accounting Journal, 2021)
The article deals with borrower-based instruments within macroprudential policy as measures aimed at reducing systemic risk regarding household debt. Our contribution is three-fold; Firstly, we show that more than 50% of countries in the European Economic Area have incorporated the borrower-based measures into their national legal framework. Secondly, we provide evidence that in countries exceeding the average level of household debt growth, more active caps are used. Thirdly, our results confirm the use of more than one active cap in countries where the house price increase was higher than average house price growth. We also highlight the reaction of the Czech National Bank and other authorities to the COVID-19 crisis, which has resulted in the relaxing of standards.
Keywords: G51; G18; 650; Household debt; Macroprudential policy; Borrower-based instrument